Electrolyte and sodium ion battery containing same

By using 5-nitroisosorbide derivatives and fluorosulfonate compounds in sodium ion batteries to form a stable SEI film, the problem of insufficient performance of sodium ion batteries at low and high temperatures is solved, and the battery is significantly improved Storage and cycling performance.

CN119133595APending Publication Date: 2024-12-13ZHUHAI SMOOTHWAY ELECTRONICS MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411199002.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The electrochemical performance of sodium ion batteries under low temperature conditions is insufficient, especially the kinetics of ion transport and electrode-electrolyte interface cationic desolvation in electrolytes, resulting in unstable SEI film formation, affecting high-temperature storage and cycling performance.

Method used

An electrolyte containing 5-nitroisosorbide derivatives and fluorosulfonate compounds as additives is used to form a dense and thermodynamically stable SEI film to improve the high-temperature and low-temperature performance of sodium ion batteries.

Benefits of technology

By optimizing the composition of the SEI film, the high-temperature storage performance, high-temperature circulation performance and low-temperature performance of sodium ion batteries are significantly improved, side reactions are slowed down, battery gas bloating is prevented, and rate performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133595A_ABST
    Figure CN119133595A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte and a sodium ion battery containing the electrolyte. The electrolyte comprises an electrolyte salt, a non-aqueous organic solvent and an additive. The additive is prepared from a 5-nitro isosorbide derivative and a fluorosulfonate compound. The structural formula of the 5-nitro isosorbide derivative is as shown in a formula I, and the structural formula of the fluorosulfonate compound is as shown in a formula II or a formula III. Wherein R1 is a group which contains an electron withdrawing group and has 1-10 carbon atoms, R2 is C1-C10 alkyl or halogen-substituted C1-C10 alkyl, and R3 and R4 are respectively and independently hydrogen, halogen, C1-C10 alkyl or halogen-substituted C1-C10 alkyl. According to the electrolyte disclosed by the invention, the low-temperature and high-temperature storage and high-temperature cycle performance of the battery can be improved through the synergistic effect of the 5-nitro isosorbide derivative and the fluorosulfonate compound. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy batteries, and in particular to an electrolyte and a sodium ion battery containing the electrolyte. Background Art

[0002] Due to the abundance of sodium resources, rechargeable sodium-ion batteries (SIBs) have been considered as ideal candidate materials for large-scale energy storage systems. However, the electrochemical performance of sodium-ion batteries under low temperature conditions (especially below -20°C) is still challenging and cannot meet the urgent needs of deployment in extreme environments. This is mainly due to the kinetic barriers of ion transport in the electrolyte, cation desolvation at the electrode-electrolyte interface, ion transport within the interface layer, and electron and ion transport within the electrode material. In addition, the interface Na + The desolvation process is more sensitive to low temperatures and induces a dominant charge transfer impedance. This slow process is conducive to the undesirable Na deposition in the incompatible solid electrolyte interface (SEI). In addition, the ideal SEI film formed by the additives in the electrolyte should be electronically insulating and ionically conductive, and should be insoluble and inert relative to the electrolyte to avoid irreversible capacity loss caused by side reactions. Compared with lithium-ion batteries, the solubility of alkyl sodium and alkyl sodium carbonate in the SEI film formed in sodium-ion batteries is 70 to 80 times higher in carbonates than that of inorganic NaF, Na2CO3, etc., and the solubility of the inorganic components NaF and Na2CO3 in Na-SEI is 30 to 40 times higher than that of the inorganic components LiF and Li2CO3 in Li-SEI, resulting in the instability of Na-SEI and an increase in side reactions with the electrolyte, which leads to the attenuation of high-temperature storage and cycle performance of sodium-ion batteries.

[0003] Therefore, there is an urgent need to develop an electrolyte that can form an excellent SEI film and a sodium ion battery containing the electrolyte to solve the shortcomings of the prior art. Summary of the invention

[0004] In view of the above problems, the object of the present invention is to provide an electrolyte and a sodium ion battery containing the electrolyte, wherein the electrolyte can promote the formation of a denser and thermodynamically stable SEI film, thereby improving the high-temperature storage performance, high-temperature cycle performance and low-temperature performance of the corresponding sodium ion battery.

[0005] To achieve the above-mentioned object, the first aspect of the present invention provides an electrolyte solution, comprising an electrolyte salt, a non-aqueous organic solvent and an additive. The additive comprises a 5-nitroisosorbide derivative and a fluorosulfonate compound. The structural formula of the 5-nitroisosorbide derivative is shown in Formula 1, and the structural formula of the fluorosulfonate compound is shown in Formula 2 or Formula 3. Wherein, R1 is a group containing an electron-withdrawing group and having 1 to 10 carbon atoms, and R2 is C1 to C 10C1~C 10 R3 and R4 are independently hydrogen, halogen, C1-C 10 C1~C 10 of hydrocarbon groups.

[0006]

[0007] Compared with the prior art, the 5-nitroisosorbide derivatives in the electrolyte of the present invention form an organic / inorganic film containing components such as alkyl sodium, sodium hydroxyl, sodium carbonate, sodium nitride, etc. at the hard carbon negative electrode during the first charging process. These components have excellent ion conduction capabilities, which enable the battery to have better rate and low temperature performance. However, components such as alkyl sodium have a large solubility in carbonates, and are unstable at high temperatures or in the late cycle. They are easily decomposed and produce CO2, which causes the battery to swell, seriously affecting the performance of the battery. Based on this, the introduction of a fluorinated sulfate solvent with a higher oxidation potential helps to form interface components with lower impedance such as sodium sulfide and sodium fluoride at the interface, further improving the ion conduction capability of the interface film. In addition, the fluorinated sulfate solvent has a lower solubility in sodium carbonate and sodium nitride, which can slow down the side reactions between the electrolyte and the hard carbon negative electrode, prevent the release of CO2, and allow the chemical reaction to reach equilibrium. Therefore, the present invention combines two compounds, 5-nitroisosorbide derivatives and substituted sulfate solvents, which can not only inhibit the gas production of the battery and improve the high-temperature storage performance and high-temperature cycle performance, but also significantly improve the low-temperature performance and rate performance of the battery. As a technical solution of the present invention, the electron-withdrawing group is a cyano group, a carbonyl group or a fluorine group, R2 is a C1-C6 hydrocarbon group or a fluorine-substituted C1-C6 hydrocarbon group, and R3 and R4 are each independently hydrogen, fluorine, a C1-C6 hydrocarbon group or a fluorine-substituted C1-C6 hydrocarbon group.

[0008] As a technical solution of the present invention, R1 is a C1-C6 alkyl group substituted with a cyano group, a C1-C6 alkyl group substituted with a fluorine group, an alkyl ketone group having 1 to 6 carbon atoms, or a fluoroalkyl ketone group having 1 to 6 carbon atoms, R2 is a C1-C6 alkyl group or a fluorine-substituted C1-C6 alkyl group, and R3 and R4 are each independently hydrogen, fluorine, a C1-C6 alkyl group, or a fluorine-substituted C1-C6 alkyl group.

[0009] As a technical solution of the present invention, the mass percentage of the 5-nitroisosorbide derivative in the electrolyte is 0.1-1.0%, and the mass percentage of the fluorosulfonate compound in the electrolyte is 5-20%.

[0010] As a technical solution of the present invention, the 5-nitroisosorbide derivative is selected from at least one of compounds 1-3.

[0011]

[0012] As a technical solution of the present invention, the fluoro sulfonate compound is selected from at least one of Compounds 4 to 7.

[0013]

[0014]

[0015] As a technical solution of the present invention, the electrolyte salt is selected from at least one of NaPF6, NaBF4, NaClO4, NaBOB, NaODFB, NaFAP, NaAsF6, NaSbF6, NaCF3SO3, NaN(SO2CF3)2, NaN(SO2C2F5)2, NaN(SO2C4F9)2, NaC(SO2CF3)3, NaPF2(C2O4)2, NaPF4(C2O4), NaB(CF3)4 and NaBF3(C2F5).

[0016] As a technical solution of the present invention, the non-aqueous organic solvent is selected from carbonates and / or carboxylates.

[0017] As a technical solution of the present invention, the non-aqueous organic solvent is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, ethyl propionate, propyl propionate and butyl propionate.

[0018] The second aspect of the present invention provides a sodium ion battery, which includes a positive electrode active material, a negative electrode active material and the foregoing electrolyte. Detailed Embodiments

[0019] The sodium ion battery of the present invention includes a positive electrode active material, a negative electrode active material and an electrolyte. The positive electrode active material can be a layered oxide, and the chemical formula of the layered oxide is Na x M (1-y-z) Fe y Mn z O2, where M includes at least one of Co, Ni, Cu, Mg, Zn, Al, Sn, Ga, Cr, Sr, V and Ti, 0 < x ≤ 1, 0 ≤ y < 1, 0 ≤ z < 1, and y + z ≤ 1. Of course, the positive electrode material can also be other materials that can undergo ion deintercalation with sodium ions. The negative electrode material includes at least one of a carbon-based negative electrode material, a titanium-based oxide negative electrode material and an alloy-based negative electrode material. Further, the negative electrode material can include hard carbon, soft carbon, sodium titanate, Sb alloy, Sn alloy, potassium alloy, aluminum alloy, copper alloy, molybdenum alloy, etc.

[0020] The electrolyte includes an electrolyte salt, a non-aqueous organic solvent and an additive.

[0021] The electrolyte salt is selected from at least one of NaPF6, NaBF4, NaClO4, NaBOB (sodium dioxalate borate), NaODFB (sodium difluorooxalate borate), NaAsF6, NaSbF6, NaCF3SO3, NaN(SO2CF3)2, NaN(SO2C2F5)2, NaN(SO2C4F9)2, NaC(SO2CF3)3, NaPF2(C2O4)2, NaPF4(C2O4), NaB(CF3)4 and NaBF3(C2F5). The concentration of the electrolyte salt in the electrolyte is 0.5-2.5 mol / L. As an example, the electrolyte salt may be, but is not limited to, 0.5 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2.0 mol / L, 2.3 mol / L, 2.5 mol / L.

[0022] The non-aqueous organic solvent is selected from carbonate and / or carboxylic acid ester. Further, the non-aqueous organic solvent is selected from at least one of ethylene carbonate (PC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, ethyl propionate, propyl propionate and butyl propionate.

[0023] The additives include 5-nitroisosorbide derivatives and fluorinated sulfonate compounds.

[0024] The structural formula of 5-nitroisosorbide derivatives is shown in Formula 1. R1 is a group containing an electron-withdrawing group and having 1 to 10 carbon atoms, and the electron-withdrawing group is cyano, carbonyl or fluorine. Furthermore, R1 is a C1-C6 alkyl group substituted with a cyano group, a C1-C6 alkyl group substituted with a fluorine group, an alkyl ketone group having 1 to 6 carbon atoms, or a fluoroalkyl ketone group having 1 to 6 carbon atoms. The mass percentage of 5-nitroisosorbide derivatives in the electrolyte is 0.1 to 1.0%. As an example, the content of 5-nitroisosorbide derivatives can be, but is not limited to, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, and 1.0%. The content of 5-nitroisosorbide derivatives should not be too low, otherwise it is difficult to form a dense SEI film on the surface of the positive electrode active material, which will affect the high-temperature storage performance and poor high-temperature cycle performance. Of course, its content should not be too high, otherwise the SEI film formed will be relatively thick, which is not conducive to improving the high-temperature storage and high-temperature cycle performance of sodium-ion batteries.

[0025]

[0026] The nitroisosorbide derivative is at least one selected from compounds 1-3.

[0027]

[0028]

[0029] Among them, compound 1 can be obtained by electrophilic addition reaction of 5-mononitroisosorbide and acrylonitrile under the catalytic action of weak base. Compound 2 can be obtained by acylation reaction of 5-mononitroisosorbide and trifluoroacetic anhydride under the catalytic action of weak base. Compound 3 can be obtained by acylation reaction of 5-mononitroisosorbide and dimethyl carbonate under the catalytic action of weak base.

[0030] The structural formula of the fluorinated sulfonate compound is shown in Formula 2 or Formula 3, wherein R2 is C1~C 10 C1~C 10 R3 and R4 are independently hydrogen, halogen, C1-C 10 C1~C 10 alkyl. Further, the electron-withdrawing group is a cyano group, a carbonyl group or a fluorine-substituted C1-C6 hydrocarbon group, and R2 is a C1-C6 hydrocarbon group or a fluorine-substituted C1-C6 hydrocarbon group, and R3 and R4 are each independently hydrogen, fluorine, a C1-C6 hydrocarbon group or a fluorine-substituted C1-C6 hydrocarbon group. Further, R2 is a C1-C6 alkyl group or a fluorine-substituted C1-C6 alkyl group, and R3 and R4 are each independently hydrogen, fluorine, a C1-C6 alkyl group or a fluorine-substituted C1-C6 alkyl group. The mass percentage of the fluorinated sulfonate compound in the electrolyte is 5-20%. As an example, the mass percentage of the fluorinated sulfonate compound can be, but is not limited to, 5%, 8%, 10%, 12%, 15%, 17%, 20%.

[0031]

[0032] The fluorinated sulfonate compound is at least one compound selected from Compounds 4 to 7.

[0033]

[0034]

[0035] For ease of understanding of the present invention, the present invention enumerates the following embodiments. Those skilled in the art should understand that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0036] Example 1

[0037] (1) Preparation of electrolyte: The electrolyte was prepared in a vacuum glove box with an argon atmosphere and a moisture content of less than 1 ppm. In a dry argon atmosphere glove box, propylene carbonate (PC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a weight ratio of PC:EMC:DEC=30:50:20. Then, additives were added, dissolved, and stirred thoroughly. Then, electrolyte salt NaPF6 was added and mixed evenly to obtain an electrolyte.

[0038] (2) Preparation of positive electrode: NaNi 0.3 Mn 0.3 Fe 0.3 O2, adhesive PVDF and conductive agent SuperP are evenly mixed in a mass ratio of 95:1:4 to form a sodium ion battery positive electrode slurry with a certain viscosity. The mixed slurry is coated on both sides of an aluminum foil, and then dried and rolled to obtain a positive electrode sheet.

[0039] (3) Preparation of negative electrode sheet: Artificial graphite, conductive agent SuperP, thickener CMC, and adhesive SBR (styrene-butadiene rubber latex) are mixed in a mass ratio of 95:1.5:1.0:2.5 to make a slurry, mix them evenly, apply the mixed slurry on both sides of the copper foil, dry and roll-press to obtain a negative electrode sheet.

[0040] (4) Preparation of sodium ion battery: The positive electrode sheet, the separator and the negative electrode sheet are stacked to form a square battery cell, which is packaged with a polymer and filled with the above-prepared electrolyte. After the steps of formation and capacity separation, a sodium ion battery with a capacity of 1500 mAh is produced.

[0041] The electrolyte formulations of Examples 1 to 12 and Comparative Examples 1 to 3 are shown in Table 1. The preparation steps of the sodium ion battery are the same as those of Example 1.

[0042] Table 1 Electrolyte formulations of various embodiments and comparative examples

[0043]

[0044]

[0045] The sodium ion batteries prepared in Examples 1 to 12 of the present invention and Comparative Examples 1 to 3 were subjected to performance tests. The test results are shown in Table 2. The test conditions are as follows.

[0046] (1) First Coulomb efficiency test

[0047] The sodium ion battery was placed in a high temperature and high pressure formation cabinet, and the battery was formed in three steps using a pressure of 25°C and 0.28Mpa (4PCS battery). The first step was 0.05C constant current for 60min, and the charging capacity C1 was recorded. The second step was 0.1C constant current for 120min, and the charging capacity C2 was recorded. The third step was 0.2C constant current for 240min, and the charging capacity C3 was recorded. The upper limit voltage was 3.9V. Then the battery was sealed twice using a rotary sealer. Then, it was charged at room temperature using a 0.5C constant current to a voltage of 4.1V, and then charged at a 4.1V constant voltage to a current of 0.05C, and then discharged at a 1C constant current to a voltage of 2.5V. The first discharge capacity C0 was recorded, and the first coulomb efficiency = C0 / (C1+C2+C3)×100%.

[0048] (2) High temperature cycle test of sodium ion battery

[0049] Place the sodium ion battery in a 45℃ constant temperature box and let it stand for 30 minutes to allow the sodium ion battery to reach a constant temperature. Charge at a constant current of 1C to a voltage of 4.0V, then charge at a constant voltage of 4.0V to a current of 0.05C, then discharge at a constant current of 1C to a voltage of 2.0V, and record the first cycle discharge capacity of the battery. This is a charge and discharge cycle. Repeat this cycle for 400 weeks, record the discharge capacity of the first cycle and the discharge capacity of the last cycle, and calculate the capacity retention rate according to the following formula.

[0050] Capacity retention rate = discharge capacity of the last cycle / discharge capacity of the first cycle × 100%

[0051] (3) Sodium ion battery high temperature storage test

[0052] At room temperature (25°C), the lithium-ion battery was charged and discharged at 0.5C / 0.5C (the battery discharge capacity was recorded as C0), with an upper limit voltage of 4.4V. The battery was then charged to 4.4V at 0.5C constant current and constant voltage, and the battery thickness was measured (the thickness was recorded as D0). The battery was placed in a 60°C oven for 30 days, taken out and the battery thickness was measured (the thickness was recorded as D1), and the thickness expansion rate was calculated.

[0053] Thickness expansion rate = (D1 / D0)*100%

[0054] (4) Low temperature discharge test

[0055] At room temperature (25°C), the sodium-ion battery was charged and discharged at 0.5C / 0.5C (the battery discharge capacity was recorded as C0), with an upper voltage of 4.1V; the battery was then placed in a low-temperature box at -10°C, and then discharged at a constant current of 0.1C to a voltage of 2.0V, and the first discharge capacity C1 of the battery was recorded. This was a charge and discharge cycle. The lithium-ion battery was charged and discharged at room temperature (25°C) at 0.5C / 0.5C (the battery discharge capacity was recorded as C2). After 10 cycles, the battery was disassembled to observe the sodium precipitation of the electrode.

[0056] Capacity recovery rate = (C2 / C0)*100%

[0057] Table 2 Electrochemical performance test results of various embodiments and comparative examples

[0058]

[0059]

[0060] From the results in Table 2, it can be seen that the sodium ion batteries of Examples 1 to 12 have good high temperature storage performance, high temperature cycle performance and low temperature performance. This is because the electrolyte of the present invention can improve the low temperature, high temperature storage and high temperature cycle performance of the battery through the synergistic effect of 5-nitroisosorbide derivatives and fluorosulfonate compounds.

[0061] By comparing Examples 1 to 3, it can be seen that the low temperature performance of the 5-nitroisosorbide derivative is better when it is compound 2, which may be related to the fact that its group contains more fluorine. Finally, it should be noted that the above examples are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. An electrolyte comprising an electrolyte salt, a non-aqueous organic solvent and an additive, characterized in that: The additive includes 5-nitroisosorbide derivatives and fluorosulfonate compounds. The structural formula of the 5-nitroisosorbide derivatives is shown in Formula 1, and the structural formula of the fluorosulfonate compound is shown in Formula 2 or Formula 3. Wherein, R1 is a group containing an electron-withdrawing group and having 1 to 10 carbon atoms, and R2 is C1 to C 10 C1~C 10 R3 and R4 are independently hydrogen, halogen, C1-C 10 C1~C 10 of hydrocarbon groups.

2. The electrolyte according to claim 1, characterized in that The electron-withdrawing group is cyano, carbonyl or fluorine, R2 is a C1-C6 hydrocarbon group or a fluorine-substituted C1-C6 hydrocarbon group, and R3 and R4 are each independently hydrogen, fluorine, a C1-C6 hydrocarbon group or a fluorine-substituted C1-C6 hydrocarbon group.

3. The electrolyte according to claim 1, characterized in that R1 is a cyano-substituted C1-C6 alkyl group, a fluorine-substituted C1-C6 alkyl group, an alkyl ketone group having 1 to 6 carbon atoms, or a fluoroalkyl ketone group having 1 to 6 carbon atoms, R2 is a C1-C6 alkyl group or a fluorine-substituted C1-C6 alkyl group, and R3 and R4 are each independently hydrogen, fluorine, a C1-C6 alkyl group, or a fluorine-substituted C1-C6 alkyl group.

4. The electrolyte according to claim 1, characterized in that The mass percentage of the 5-nitroisosorbide derivative in the electrolyte is 0.1-1.0%, and the mass percentage of the fluorosulfonate compound in the electrolyte is 5-20%.

5. The electrolyte according to claim 1, characterized in that The 5-nitroisosorbide derivative is selected from at least one of compounds 1 to 3, 6. The electrolyte according to claim 1, characterized in that The fluorinated sulfonate compound is selected from at least one of compounds 4 to 7:

7. The electrolyte according to claim 1, characterized in that The electrolyte salt is selected from at least one of NaPF6, NaBF4, NaClO4, NaBOB, NaODFB, NaFAP, NaAsF6, NaSbF6, NaCF3SO3, NaN(SO2CF3)2, NaN(SO2C2F5)2, NaN(SO2C4F9)2, NaC(SO2CF3)3, NaPF2(C2O4)2, NaPF4(C2O4), NaB(CF3)4 and NaBF3(C2F5).

8. The electrolyte according to claim 1, characterized in that The non-aqueous organic solvent is selected from carbonates and / or carboxylates.

9. The electrolyte according to claim 8, characterized in that The non-aqueous organic solvent is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, ethyl propionate, propyl propionate and butyl propionate.

10. A sodium ion battery comprising a positive electrode active material, a negative electrode active material and the electrolyte according to any one of claims 1 to 9.